Historical Geographical Information System (HGIS): social trajectories of two Chinese historical figures Su Shi and Zuo Zongtang in spatial context - Fu, Jing; Chen, Kangsheng; Qin, Jianxin; Yang, Liguo; Liu, Peilin; Zheng, Wenwu (Heritage science, 2024)
Historical figures have important significance worldwide. This paper introduces the concept of historical Geographical Information System (HGIS) using the lives of two personalities from Chinese history as case studies: Su Shi, a literary figure of the Northern Song Dynasty, and Zuo Zongtang, a military strategist from the late Qing era. By studying the geographical points marking their life activities, their migratory patterns were explored, along with the dynamics of their social networks within time and space, examining the distinctive phases and characteristics of their individual journeys. Kernel density estimation, standard deviation ellipse, location-based distance analysis, and social network graphs were employed in this work. Our findings reveal that Su Shi’s migrations were largely dictated by official appointments, ultimately rooted in imperial successions and factional strife, with his intellectual pursuits significantly influenced by the humanistic milieu. Conversely, Zuo Zongtang’s migrations were predominantly shaped by war, reflecting the challenges of the late Qing era in relation to governance, sovereignty, and diplomacy. The military encampments selected by Zuo Zongtang tended to be situated near water sources, illustrating how his migratory trajectory was influenced by natural geographic conditions. The social circles of these figures are tied to their social and political stature. Through the socio-historic context, the characteristics of these historical figures’ behavioral trajectories relate to the unfolding process of societal and historical development. These insights offer a glimpse into the life journey behind historical figures, implicitly highlighting their perseverance and resilience in adversity, thereby describing innovative approaches to inheriting and disseminating the cultural legacy.